PRELIMINARY PHYTOCHEMICAL SCREENING AND ANTIMICROBIAL ACTIVITY OF DRIED FLOWERS OF ADENIUM OBESUM - KALVA, SIREESHA; N., RAGHUNANDAN (International Journal of Current Pharmaceutical Research, 2019)
Objective: To estimate the antimicrobial activity of methanolic extract of Adenium obesum (family Apocyanaceae) in association with phytochemical analysis. Methods: The methanolic extract of the flowers of Adenium obesum was prepared and investigated for phytochemical constituents using standard methods. Antimicrobial activity of methanolic extract Adenium obesum has been carried out against one gram-positive bacteria Staphylococcus aureus and one gram-negative bacteria Escherichia coli and the antifungal activity of the plant extract was evaluated on Candida albicans species. The testing was done by the disc diffusion method to visualize the zone of inhibition of methanolic extract was compared with that of standard drug i.e., Ciprofloxacin for antibacterial activity and Fluconazole for antifungal activity. The minimum inhibition concentration was determined by micro dilution method (cup-plate method). Results: The present investigation shows the phytochemical analysis confirmed the presence of alkaloids, saponin glycosides, flavonoids, phenols, proteins and amino acids, cardiac glycosides, steroids, tannin, and phenolic compounds. The anti-microbial activity of the methanolic extract of the plant showed significant results against all the three of the test organisms in compare to the standard drugs. Conclusion: The present study concluded that methanolic extract of the flowers of adenium obesum proved the existence of phytochemical constituents. The methanolic extract of the was found to possess promising antimicrobial activity when compared with the standards and it can be useful for the development of antibiotics.